Prospective Position of Humanoid Robots as Subjects of Criminal Law in Indonesia - Renfred Valdemar; Mompang. L. Panggabean; Richard. M. Nainggolan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The advancement of Artificial Intelligence (AI) technology in the form of humanoid robots (human-like robots) has led to numerous incidents and violations of criminal law, often caused by the actions of the humanoid robots themselves. This has given rise to debate among experts as to who is responsible for these violations. Indonesian Criminal Law stipulates that the subjects of criminal law are humans and legal entities. Meanwhile, the position of AI robots within the Indonesian legal framework (UU ITE) is as an 'electronic agent' which is an electronic system device controlled by an individual or institution/corporation. If examined more closely, technically, humanoid robots have almost the same capabilities as humans to think and move independently (autonomous) without being driven or by anyone. The concept of criminal law stipulates that to determine a crime must look at the element of the perpetrator's mental condition (mens rea). If a criminal offense is committed by a humanoid robot that does not have a natural mental condition, can it be categorized as a crime and who should be held responsible? Because there is no consensus yet on whether the subject of criminal law is appropriate to be assigned to humanoid robots, this study will discuss briefly and concisely the prospective position of humanoid robots as subjects of criminal law in Indonesia.